Early transoesophageal echocardiography in cryptogenic and lacunar stroke and transient ischaemic attack. Issue 5 (1st May 1998) - Censori, Bruno; Colombo, Francesca; Valsecchi, Maria Grazia; Clivati, Laura; Zonca, Anna; Camerlingo, Massimo; Casto, Luciano; De Tommasi, Mario Salvatore; Mamoli, Angelo
Abstract : OBJECTIVES: To test the hypothesis that transoesophageal echocardiography (TOE) carried out within three days of a first stroke or transient ischaemic attack of cryptogenic or lacunar type may disclose more thrombi or spontaneous echo contrast (SEC) than previously reported. This finding may help early treatment decisions. METHODS: Patients aged between 40 and 80 years, admitted for transient ischaemic attack or ischaemic stroke during a 40 month period, were prospectively considered. TOE was carried out within 72 hours of symptom onset with a 5 MHz biplanar transducer. Subjects with recurring events, very severe strokes, large artery obstructions, or obvious cardiac sources of embolism were excluded. RESULTS: Sixty five patients were studied, 43 with a cryptogenic stroke or transient ischaemic attack (66.2%), and 22 with a lacunar stroke (33.8%). The mean (SD) interval between symptom onset and TOE was 43.4 (17.2) hours for cryptogenic, and 48.5 (19.5) hours for lacunar patients. Atrial thrombi were found in one patient with a cryptogenic stroke (2.32% of cryptogenic events; 95% confidence interval 0.06–12.29), whereas SEC was found in five patients (7.7% overall), two with a lacunar and three with a cryptogenic stroke. CONCLUSIONS: An early TOE does not seem to increase substantially the detection of atrial thrombi or SEC in patients with a first stroke or transient ischaemic attack of cryptogenic or lacunar nature. Therefore, this examination can be carried out when the patients' conditions are stable, and without overloading the cardiovascular laboratory daily schedule.